UV-Activated Luminescence/Colourimetric O2 Indicator - Andrew Mills; Cheryl Tommons; Raymond T. Bailey; M. Catriona Tedford; Peter J. Crilly (International Journal of Photoenergy)
An oxygen indicator is described, comprising nanoparticles of titania dispersed in hydroxyethyl cellulose (HEC) polymer film containing a sacrificial electron donor, glycerol, and the redox indicator, indigo-tetrasulfonate (ITS). The indicator is blue- coloured in the absence of UV light, however upon exposure to UV light it not only loses its colour but also luminesces, unless and until it is exposed to oxygen, whereupon its original colour is restored. The initial photobleaching spectral (absorbance and luminescence) response characteristics in air and in vacuum are described and discussed in terms of a simple reaction scheme involving UV activation of the titania photocatalyst particles, which are used to reduce the redox dye, ITS, to its leuco form, whilst simultaneously oxidising the glycerol to glyceraldehye. The response characteristics of the activated, that is, UV photobleached, form of the indicator to oxygen are also reported and the possible uses of such an indicator to measure ambient O2 levels are discussed.